Oropouche Virus Isolation, Southeast Brazil - Nunes, Márcio Roberto Teixeira (Centers for Disease Control and Prevention, 2005)
An Oropouche virus strain was isolated from a novel host (Callithrix sp.) in Arinos, Minas Gerais State, southeastern Brazil. The virus was identified by complement fixation test and confirmed by reverse transcription–polymerase chain reaction. Phylogenetic analysis identified this strain as a genotype III isolate previously recognized only in Panama.